Effectiveness of Restorative Justice Principles in Juvenile Justice: A Meta-Analysis - Wilson, David B. ([Verlag nicht ermittelbar], 2018)
The objective of this study was to systematically review and statistically synthesize all available research that, at a minimum, compared participants in a restorative justice program to participants processed in a more traditional way using meta-analytic methods. Ideally, these studies would include research designs with random assignment to condition groups, as this provides the most credible evidence of program effectiveness. The systematic search identified 99 publications, both published and unpublished, reporting on the results of 84 evaluations nested within 60 unique research projects or studies. Results were extracted from these studies, related to delinquency, non-delinquency, and victim outcomes for the youth and victims participating in these programs.